2023
DOI: 10.2147/cia.s388469
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Multimorbidity Among the Oldest Old: Study Findings from the Representative “Survey on Quality of Life and Subjective Well-Being of the Very Old in North Rhine-Westphalia (NRW80+)”

Abstract: Purpose Our aim was to clarify the frequency and correlates of multimorbidity among the oldest old. Patients and Methods We used data from the representative “Survey on quality of life and subjective well-being of the very old in North Rhine-Westphalia (NRW80+)” covering participants ≥80 years living in private households and in institutionalized settings in North Rhine-Westphalia (n = 1484, mean age was 86.3 years). Multimorbidity is defined as the co-occurrence of at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Research has shown that mental health symptoms change over time, especially when individuals transit from old to oldest old [ 18 ]. At the same time, more depressive symptoms are significantly associated with multimorbiditiy among oldest-old individuals [ 19 ]. Concerning the study aim, somatization was the only outcome that appeared to be affected by BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that mental health symptoms change over time, especially when individuals transit from old to oldest old [ 18 ]. At the same time, more depressive symptoms are significantly associated with multimorbiditiy among oldest-old individuals [ 19 ]. Concerning the study aim, somatization was the only outcome that appeared to be affected by BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between job stress, quality of life, and well-being. Hajek and K€ onig (2023) suggested that well-being is a subjective emotional state associated with a person's self-rated quality of life as well as positive and negative emotions. Well-being is an important health indicator of employees, and it can be viewed as the overall quality of life as rated by the individual (Hammoudi et al, 2023).…”
Section: 12mentioning
confidence: 99%
“… 3 Furthermore, sociodemographic variables such as loneliness, 4 higher pain, 5 nursing home admission, 6 high economic burdens, 7 and even mortality, 8 other living situation and network size were associated with multimorbidity among the oldest old. 9 This challenge has broad implications for individual, family, community, and state life well-being, particularly in low- and middle-income nations such as Indonesia.…”
Section: Introductionmentioning
confidence: 99%